An Analysis of the Relationship between Students’ Scientific Attitude and Students’ Learning Style in Junior High School - Ikmanda Nugraha; Nabilah Kinanti Putri; Hayat Sholihin (Universitas Pendidikan Indonesia, 2020)
The objectives of this study were to profile the relationship of scientific attitude level and learning style preference among junior high school students in Bandung. This study utilized a survey research design with a total sample size of 110 students. A scientific attitude questionnaire and a visual, auditory, and kinesthetic (VAK) learning style inventory were administered in this study. The questionnaire measures five aspects of scientific attitude, specifically rationality, curiosity, open-mindedness, aversion to superstition, and objectivity. The VAK learning style inventory evaluates the preferred means of receiving sensory information. The scientific attitude questionnaire provided consistent results, as indicated by its reliability coefficient (0.896). The results show that junior high school students have an average level of scientific attitude and generally prefer a kinesthetic learning style. There was a medium relationship between scientific attitude and learning style among the students (Cramer’s V coefficient = 0.239). It is concluded that learning style must be considered in implementing a science lesson, especially in the Indonesian context.